ANALISIS HUKUM TEHADAP PENGARUH KEBIJAKAN TATA RUANG TERHADAP PENGELOLAHAN LINGKUNGAN BERBASIS AMDAL - Hs, Fatimah; Kurenteng, Pinkan Jonike; Pangemanan, Injil Yesika Krisia; Thomas, Andini Dewi (Gapenas Publisher, 2025)
Spatial planning policy plays a fundamental role in directing sustainable development and ensuring balance between land use and environmental protection. This study aims to analyze the influence of spatial planning policy on the effectiveness of environmental management based on Environmental Impact Assessment (EIA), focusing on the integration between Regional Spatial Plans (RTRW), Detailed Spatial Plans (RDTR), and EIA within Indonesia’s legal and institutional framework. The research employed a juridical-normative approach supported by contextual analysis of institutional data and environmental planning documents in North Sulawesi Province. The analysis was conducted through legal document review, normative interpretation, and policy comparison across levels of government. The results show that integration between RTRW/RDTR and EIA remains ineffective due to regulatory disharmony, weak institutional coordination, and limited spatial data availability. The functional relationship between Approval of Spatial Utilization Conformity and Environmental Approval, which should be sequential, often operates separately in practice. The analytical model indicates that spatial data readiness and institutional capacity have a direct influence on policy integration effectiveness, while cross-sectoral coordination serves as a mediating factor that strengthens inter-agency synergy. These findings emphasize the need for regulatory harmonization, institutional strengthening, and the acceleration of the One Map Policy implementation as a foundation for evidence-based decision-making. This study contributes to the understanding of adaptive and ecologically just environmental governance within Indonesia’s spatial planning system.